Cost accounting - Rajasekaran, V.; Lalitha, R. (Pearson, 2010)
The book sets a new standard for cost accounting textbooks. It aims at equipping students with a solid grounding in the concepts of cost accounting. With rich pedagogy and an easy-to-understand approach, it meets the specific requirements of the undergraduate students of different Indian universities. This book can also be useful for the students of CA, CS, MBA and ICWA level of Indian universities.